Sustainable Heritage Conservation between Declarations and Tensions: Opportunities and Limits of Community Engagement - Buivydaitė, Toma (Acta humanitarica academiae Saulensis, 2026)
This article examines the issue of community engagement in heritage conservation processes, which is increasingly presented today as one of the key prerequisites for sustainable heritage conservation. Sustainable heritage conservation is understood here as a process that integrates the protection of cultural heritage, the cultivation of cultural identity, and the empowerment of communities. Although official cultural heritage policy discourse consistently declares the goal of community inclusion, in practice participation often remains limited, shaped by institutional control or highly formalized mechanisms.The article analyses three interrelated levels: how the concept of sustainability has become established within heritage conservation discourse; how community engagement is articulated in political and legal practice; and how these principles encounter real tensions and conflicts.At the first level, the article discusses how the concept of sustainability has evolved from a narrow ecological perspective into a broader framework encompassing cultural policy and principles of participation. The second level reveals how community participation is formally constructed within political and legal arenas, often being confined to procedural forms of inclusion. At the third level, the article explores how these discrepancies become visible in situations of conflict. Drawing on critical heritage studies, conflict is understood not as a malfunction of the heritage conservation system but as an inevitable practice arising from competing interests, value frameworks, and power positions. Conflicts over heritage values, interpretations, and decision-making authority allow heritage to be seen not as a fixed object but as a field of negotiation in which the right to speak on behalf of heritage is contested.
Keywords: sustainable heritage conservation; community engagement; cultural heritage policy; participation; heritage conflicts